Pengaruh Aktivitas Pengendalian terhadap Risiko Penyalahgunaan Aset pada Bank Perkreditan Rakyat (BPR) - Hera Khairunnisa; Sumardi; Bambang Tutuko; Christian Wiradendi Wolor (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
The purpose of this study was to analyze the effect of control activities on the risk of asset misappropriation in Rural Credit Banks (BPR). This study uses a survey method using some questionnaires. The questionnaires were distributed to 30 BPR employees in most Jabodetabek areas. The collected questionnaires were analyzed using multiple regression analysis. Control activity variables are adopted from the COSO internal control framework. Control activity variables are devided into three sub-variables. Asset misappropriation in this study uses indicators from the previous studies. Measurement of control activity variables and risk of asset misappropriation in this study using a likert scale, 1 means strongly disagree and 5 means strongly agree. The results of the study indicate that the development of internal control activities has an effect on the risk of asset misuse in BPR. While the variable development of technology-based control activities and the variable realization of control activities have no effect on the risk of misuse of assets in BPR.